Upaya pengendalian pencemaran logam merkuri terhadap kegiatan pertambangan emas skala kecil : systematic review - Mahendra, Lalu Riza; Sukesi, Tri Wahyuni; Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2025)
Mercury waste pollution is an environmental health issue resulting from poor management of mineral production waste materials. Small-scale gold mining areas using amalgamation techniques still contribute high levels of mercury waste to the environment. The technical issue of inadequate storage of production waste materials warrants adaptive control studies for small-scale gold miners (PESK). The aim of this research is to determine the efficiency of chemical and biological mercury waste control in small-scale gold mining cases. This research is a literature review using the systematic review method. The obtained articles underwent review, analysis, and comparison of the systematic capabilities of chemical and biological control. The results of this research found 11 relevant study articles published between 2017-2024. Chemical and biological control methods are capable of reducing mercury levels in tailing water by up to 99%. The form of adaptive control for small-scale gold mining conditions is assessed pragmatically and based on reduced mercury levels. The conclusion of this research is that applied research on mercury waste pollution cases in small-scale mining is still relatively lacking. Efficiency in controlling mercury levels is more realistic using biological control. Laboratory test result approaches can indicate the potential of biological control with bioremediation techniques as an efficient adaptive control effort for small-scale gold miners.